A chromosomal-level genome assembly of the tropical sea cucumber Stichopus fusiformiossa - Nyok-Sean Lau; Noorizan Miswan; Nurlina Rosli; Sixu Gong; Izzat Irfan; Mathan Ganasan; Sau Pinn Woo; Annette Jaya-Ram (Scientific Data)
Abstract The genus Stichopus comprises sea cucumber species that are ecologically and economically valuable, known for their roles in nutrient cycling and as sources of bioactive compounds in traditional medicine. Genomic insights are essential for understanding the molecular pathways and biological functions underlying their adaptation, resilience, and ecological significance. We present a chromosome-level genome assembly for the tropical sea cucumber Stichopus fusiformiossa, constructed using Nanopore long-read and Hi-C sequencing. The genome assembly spans 766.55 Mb, with a scaffold N50 of 31.80 Mb, and is anchored to 23 pseudo-chromosomes. Genome completeness analysis with BUSCO revealed 98.1% of conserved metazoan genes, reflecting the assembly’s quality. Nanopore Iso-Seq analysis of muscle, intestine, and respiratory tree samples generated 10,419-35,371 non-redundant full-length isoforms, which were integrated into genome annotation, enabling the annotation of 27,991 protein-coding genes in the genome. This high-quality genome assembly and Iso-Seq transcriptome data provide a valuable resource for advancing genetic and functional studies in S. fusiformiossa, supporting future research into its unique biological traits and potential applications.